EFFECT OF INSECURITY ON LIVELIHOOD ACTIVITIES IN DUTSIN-MA LOCAL GOVERNMENT AREA, KATSINA STATE - AUWAL, ISYAKU; YERIMA , EMMANUEL GYONG; ALIYU, TANKO AHMED (JOURNAL OF ECONOMICS AND ALLIED RESEARCH, 2024)
This paper investigated the effect of insecurity on livelihood activities Dutsin-Ma local government area, Katsina State. The method of data collection was survey questionnaires that were administered to 240 respondents across the four wards in the study area. These include Dutsin-Ma A, Dutsin-Ma B, Shema and Dabawa. The analytical technique used was descriptive statistics and chi-square test using IBM SPSS Statistics 20. The theoretical framework for the study is the frustration aggression hypothesis and human security theory. The descriptive statistics made use of the linkert scale. The findings reveal that 99.1% of insecurity challenges were made up of kidnappings Killings, attacks on farm crops and cattle rustling also form 91.1%, 79.1 and 60.7% of insecurity respectively. The findings indicate that insecurity has impacted negatively on the livelihoods of 84.1% of people in the study area and has reduced the level of income of 98.1% people in the study area. The test of hypothesis reveal that that insecurity has negative effects on livelihood activities in Dutsin-Ma local government area of Katsina State Nigeria. From the findings, the study was able to establish that there is a high level of insecurity in the study area. Creating fear and lack of confidence among the people in carrying out their activities. Therefore there is need for a robust security structure in the study area. This could come through community policing and liaison with Nigerian Police Force in the study area to form a strong and fearless team that can confront the perpetrators of insecurity. Intelligence information to security agencies should be provided by the citizens, but their privacy should be respected